I am currently studying the lecture note from Jesus. In page 49, he provides 4 equilibrium conditions:

$$\frac1{c_t} = \beta E_t\left\{\frac1{c_{t+1}}\left(1 + \alpha e^{z_{t+1}}k_{t+1}^{\alpha -1}l_{t+1}^{1-\alpha} - \eta\right)\right\}$$ $$\frac{1-\xi}{1-l_t} = \frac{\xi}{c_t}(1-\alpha) e^{z_t} k_t^{\alpha} l_{t}^{-\alpha}$$ $$c_t + k_{t+1} = e^{z_t}k_t^{\alpha}l_t^{1-\alpha} + (1-\eta) k_t$$ $$z_t = \rho z_{t-1} + \varepsilon_t$$

Then, in page 50, he says that with $\eta=1$, we have $$l_t = l = \frac{(1-\alpha)\xi}{(1-\alpha)\xi + (1-\xi)(1-\alpha\beta)}$$ $$k_{t+1} = \alpha \beta e^{z_t}k_t^{\alpha} l^{1-\alpha}$$

I am not sure how we derive these. With $\eta = 1$, the Euler is reduced to $$\frac1{c_t} = \alpha \beta E_t \left\{\frac{e^{z_{t+1}}k_{t+1}^\alpha l_{t+1}^{1-\alpha} }{k_{t+1} c_{t+1}}\right\}$$ and the budget constraint is reduced to $$c_t + k_{t+1} = e^{z_t}k_t^\alpha l_t^{1-\alpha}$$ I am playing with these two equations, but can't figure it out.

New contributor
muz1991 is a new contributor to this site. Take care in asking for clarification, commenting, and answering. Check out our Code of Conduct.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Browse other questions tagged or ask your own question.